Spectrum Access Algoritbm Based on POMDP Model in CVANET - Xuefei Zhang; Guoan Zhang; Yancheng Ji (Dianxin kexue)
For the dynamic features of cognitive vehicular Ad Hoc network（CVANET）channel state, a study on spectrum sensing and access of cognitive vehicle users was presented, which was based on framework of partially observable Markov decision process（POMDP）. Then, a decentralized opportunity spectrum access based on POMDP model was proposed. Because there is a huge computational complexity, the greedy algorithm was sought. Finally, the influence factors of cognitive vehicle user throughput through the simulation were studied, and the feasibility of the algorithm was verified. The simulation results show that cognitive vehicle user's access throughput is effectively improved by this algorithm which avoid the happening of broadcast storm and also simplify the calculation.